Management of Physical Education Laboratory Facilities and Infrastructure at PGRI University Palembang - Khalipah, Khalipah; Manullang, Jujur Gunawan; Junaidi, Ilham Arvan (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to create an article entitled Management of Physical Education Laboratory Facilities and Infrastructure at PGRI University Palembang, kThe implementation of the Physical Education teaching and learning process in the Faculty of Teacher Training and Education, Palembang PGRI University is inseparable from the availability of good and adequate infrastructure. Good and adequate infrastructure will make the physical education learning process run well which is currently very much needed in physical learning to balance theory and practice. Good. Facilities and infrastructure are one of the important factors needed in the physical education learning process. In this study using qualitative data and data sources while collecting data through observation and interviews.